Understanding Small Business Scams - Schaper, Michael; Weber, Paull (World Scientific Publishing, 2012)
This paper provides an overview of the current state of knowledge about small business scams. A scam is a form of dishonest action, based upon an invitation to participate in an activity. Victims are encouraged, mislead or induced to voluntarily interact with the perpetrator, and ultimately to willingly surrender over money, information or other valuable resources. Common forms of scams directed towards small business include phishing, false business valuations and sales, fake overpayments, false directory and advertisement listings, bust-outs, blowing, cramming, advance fee fraud and misleading self-employment projects. The limited research evidence available to date suggests that small enterprises are particularly vulnerable to these types of criminal activity, are less inclined to report such events, are likely to be subject to repeat attacks, and are particularly susceptible to online scams. This occurs because small businesses often lack the in-house skills, resources and reporting arrangements needed to effectively detect and prevent scams. The paper also briefly examines the entrepreneurial nature of scammers, and explores some of the emergent literature on the psychology of small business scams that may explain scam propensity. Strategies for combating and avoiding scams are discussed, as are suggestions for future research directions in the area.